The impact of quality dimensions of accounting information system success on the effectiveness of during-financial crisis management: The mediating role of system usage in a government sector context - Dalloul, Mahmoud Hany M; Ibrahim, Zuraeda binti; Urus, Sharina Tajul (Asian Economic and Financial Review, 2023)
The primary purpose of this research is to explore the value of quality dimensions of accounting information systems (AIS) success, as represented by system quality (SQ), information quality (IQ) and service quality (SVQ), on the effectiveness of management during financial crises. This paper highlights the mediation role of system usage (SU) in those associations in the context of a government ministry. Descriptive analytical and quantitative approaches were adopted, using a questionnaire as the data collection instrument and selecting employees of the Palestinian Ministry of Finance as a population sample for the research. A total of 141 questionnaires were distributed, of which 105 were valid for statistical analysis. In the data analysis, the partial least squares (PLS) and structural equation modelling (SEM) techniques were adopted using SmartPLS software. The results indicate a direct significant effect between SQ, IQ, SVQ, and managing during financial crises in the research context. The mediation of SU in the influence between IQ, SQ, and managing during financial crises in the governmental context is clear. Conversely, this mediation was not demonstrated in the effect of SVQ. The research emphasizes the necessity of adopting high-quality AIS in terms of SQ, IQ and SVQ because of their critical role in enhancing management effectiveness during a financial crisis. The advancement and wider employment of AIS that have high-quality characteristics can improve management tasks during a financial crisis, increasing the ability to contain the crisis and reduce its broader repercussions.